The exploration of phytocompounds theoretically combats SARS-CoV-2 pandemic against virus entry, viral replication and immune evasion. Issue 1 (January 2023) - Chen, Ting-Hsu; Tsai, May-Jywan; Chang, Chun-Sheng; Xu, Linxi; Fu, Yaw-Syan; Weng, Ching-Feng
Abstract: Background: The novel coronavirus disease-2019 (COVID-19) that emerged in China, is an extremely contagious and pathogenic viral infection caused by the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) that has sparked a global pandemic. The few and limited availability of approved therapeutic agents or vaccines is of great concern. Urgently, Remdesivir, Nirmatrelvir, Molnupiravir, and some phytochemicals including polyphenol, flavonoid, alkaloid, and triterpenoid are applied to develop as repurposing drugs against the SARS-CoV-2 invasion. Methods: This study was conducted to perform molecular docking and absorption, distribution, metabolism, excretion and toxicity (ADMET) analysis of the potential phytocompounds and repurposing drugs against three targets of SARS-CoV-2 proteins (RNA dependent RNA polymerase, RdRp, Endoribonclease, S-protein of ACE2-RBD). Results: The docking data illustrated Arachidonic acid, Rutin, Quercetin, and Curcumin were highly bound with coronavirus polyprotein replicase and Ebolavirus envelope protein. Furthermore, anti- Ebolavirus molecule Remedesivir, anti-HIV molecule Chloroquine, and Darunavir were repurposed with coronavirus polyprotein replicase as well as Ebolavirus envelope protein. The strongest binding interaction of each targets are Rutin with RdRp, Endoribonclease with Amentoflavone, and ACE2-RBD with Epigallocatechin gallate. Conclusions: Taken altogether, these results shed a light on that phytocompounds have a therapeutic potential for the treatment of anti-SARS-CoV-2 may base on multi-target effects or cocktail formulation for blocking viral infection through invasion/activation, transcription/reproduction, and posttranslational cleavage to battle COVID-19 pandemic. Graphical Abstract: ga1 Highlight: In silico discovers the potential phytocompounds combating high-infection virus. 3D mapping exerts the specific banding site of SARS-CoV-2 with potential anti-virus drugs Phytomedicines interrupt and hinder virus-entry, viral replication and immune evasion of COVID-19.